Descola’s Model Of Religion and Nature Examined - Kupakwashe Mtata (Modern Africa)
Philippe Descola suggested a scheme to enumerate dispositions to nature in such a way as to take into account non-Western practices that tend to be overshadowed by the dominance of naturalism. He also deployed this scheme to account for other religious types in the world, which in the same manner tend to be obscured by Western Christianity. This article examines Descola’s ontological scheme in the light of the case of the Mwali cult in the Matobo Hills World Heritage Site in Zimbabwe. Data gathered through a protracted period of participant observation and interviews in Matobo Hills shows that instead of the fourfold scheme Descola proposes, his reference to incarnation and figuration is a more promising avenue in an attempt to account for religious forms and the various ways humans relate to their environments.